Sekolah Sepak Bola Di Bangkinang Dengan Pendekatan Arsitektur Tropis - Arif Rahman Hakim; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Football is a sport that is highly preferred by people of all ages and all economic levels, this shows how football has a very good potential if developed properly. As one of the countries that have high interest in football, the lack of achievement of the Indonesian national team in the international arena is a problem that must be solved if one day want to see Indonesia to look up. Football School is the solution of various problems related to time and a long process to improve football coaching system in Indonesia. With the SSB is expected to produce a professional soccer player who can compete in the international arena. Bangkinang as one of the cities that have a lot of young talent and high interest will be football should play an active role in improving the football coaching system in Indonesia. In designing this SSB, tropical architecture approach is used to address a variety of issues related to climate conditions that affect the site. Some of Tropical Architecture principles applied in the design, such as: (1) orientation of the building; (2) Optimizing the shape of the stage; (3) Percentage of green spaces; (4) responsive to environmental conditions. Shoot On Target concept was chosen to solve the various problems that arose during the design process this Soccer School. This concept is applied in all aspects of the architectural design of this SSB, such as: order of mass, mass formation, landscape and interior arrangement, up to building facades. Order mass that has movement, a simple mass formation, structuring landscape and an attractive interior and facade are adapted to environmental conditions is the result of applying the concept of Shoot On Target in the design Football School in Bangkinang.Keyword: Football School, Tropical Architecture, Shoot On Target.